Low Temperature Corrosion: Oxidation of Carbon Steel and Stainless Steel in Air - Krungkarnchana, Harich; Kongvarhodom, Chutima (Applied Science and Engineering Progress, 2019)
An on-line corrosion monitor based on the principle of produced hydrogen effusion through a pipe wall due to the flow accelerated corrosion has been designed in an operating cycle mode which is complex. Using AISI 1045 and AISI 304 steels as material of probe equipped with this monitor expects to reduce the complexity of this system, the continuous mode. Type, characteristic and thickness of oxides formed on both steel surfaces affect the measurement of the rate of hydrogen production from the corrosion inside the pipe. Formation of oxides on AISI 1045 and AISI 304 at 673 K for 168 and 720 h in air was studied to determine type and thickness of oxides formed on steel surfaces under different exposure times. Oxidation of steels was performed in the heated air inside the furnace. The oxide formed on AISI 1045 surface was magnetite with different sizes of oxide particles because of the different exposure times. The oxide formed on AISI 304 surface was found as iron oxide and chromium oxide for 720 h. The thicknesses of oxides formed on AISI 1045 were 2.92 μm and 6.22 μm for 168 and 720 h, respectively. While the thicknesses of oxides formed on AISI 304 were not determined due to the irregular characteristic of oxide formed. Type and thickness of oxides obtained from this research could be used to predict the hydrogen pressure inside AISI 1045 and AISI 304 probes.